2008
DOI: 10.1093/aob/mcn133
|View full text |Cite
|
Sign up to set email alerts
|

Intrapopulation Genome Size Dynamics in Festuca pallens

Abstract: Analysis of double-peaks showed that genome size varied up to 1.188-fold within all 562 seedlings, 1.119-fold within the progeny of a single maternal plant and 1.117-fold in seedlings from grains of a single inflorescence. Generally, genome sizes of seedlings and their mothers were highly correlated. However, in maternal plants with both larger and smaller genomes, genome sizes of seedlings were shifted towards the population median. This was probably due to the frequency of available paternal genomes (pollen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 32 publications
4
36
1
Order By: Relevance
“…The results of our experiments provide clear evidence of stabilizing selection acting on genome size. This study provides experimental support for our previous observations of stabilizing selection in this population, which were based on a discrepancy in the maximum genome size range between the progeny of 17 maternal plants and established plants in the natural population (Šmarda et al. , 2008b).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The results of our experiments provide clear evidence of stabilizing selection acting on genome size. This study provides experimental support for our previous observations of stabilizing selection in this population, which were based on a discrepancy in the maximum genome size range between the progeny of 17 maternal plants and established plants in the natural population (Šmarda et al. , 2008b).…”
Section: Discussionsupporting
confidence: 86%
“…The coefficient of variation of the sample and standard peaks averaged 1.57% across 626 measurements within the competition experiments and 1.80% across 282 measurements within the germination experiment (Supporting Information Tables S1, S2). With a similar measurement accuracy using the same instrument and methods, we have repeatedly shown that, in F. pallens (and in this study population in particular), the relative genome sizes as measured using DAPI dye are closely correlated with the absolute DNA content as estimated with propidium iodide; the results are repeatable in different seasons (Šmarda & Bureš, 2006; Šmarda et al. , 2008b), and the differences between samples based on individual measurements agree well with the differences obtained in simultaneous analyses of co‐chopped samples (double peaks; Šmarda et al.…”
Section: Methodssupporting
confidence: 65%
See 1 more Smart Citation
“…Smarda et al [35] investigated differential seedling survival in a tetraploid Festuca pallens population with up to 1.189-fold genome size variation at constant chromosome number of 2n = 28. In this case, during development of the plants those with the lowest and the highest C-values were eliminated under conditions of intraspecific competition for resources.…”
Section: Journal Of Botanymentioning
confidence: 99%
“…Â DNA content ( pg) [40]. Additionally, M. filicifolius seeds were pooled with the GB population of M. laciniatus seeds and analysed using FCM to verify genome size differences through analysis of double peaks [41]. Sample and solution preparation and FCM analyses were performed as in McIntyre [42].…”
Section: Introductionmentioning
confidence: 99%